Efficacy of Plectranthus glandulosus (Lamiaceae) and Callistemon rigidus (Myrtaceae) Leaf Extract Fractions to Callosobruchus maculatus (Coleoptera: Bruchidae). Issue 1 (2nd October 2015) - Danga, Simon Pierre Yinyang; Nukenine, Elias Nchiwan; Younoussa, Lame; Adler, Cornel; Esimone, Charles Okechukwu
Abstract : As part of on-going efforts to use eco-friendly alternatives to chemical pesticides, methanol crude extracts of Plectranthus glandulosus and Callistemon rigidus leaves were sequentially fractionated in hexane, chloroform, ethyl acetate, and methanol to establish the most active fraction(s) against Callosobruchus maculatus in cowpea. Cowpea seeds (25 g) were treated with 0.5, 1, 2, and 4 g/kg of extract to evaluate the contact toxicity and F1 progeny production of the beetles in the laboratory. Mortality was recorded 1, 3, and 7 d postexposure. P. glandulosus hexane fraction was more toxic than the other fractions recording 100% mortality at 4 g/kg, within 7 d with LC50 of 0.39 g/kg. Hexane fraction of C. rigidus showed superior toxicity, causing 100% mortality at 4 g/kg within only 1 d of exposure with LC50 of 1.02 g/kg. All the fractions greatly reduced progeny emergence, with C. rigidus hexane fraction being the best progeny inhibitor. Fractions of P. glandulosus and C. rigidus leaves had sufficient efficacy to be a component of storage pest management package for C. maculatus.